THE EFFECT OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT ON SERVICE QUALITY WITH SATISFICATION AS A MODERATING VARIABLE - Ferdinand Salomo Leuwol; Asraf Asraf; Budi Sulistiyo Nugroho; Sumardi Sumardi; Idam Wahyudi (ITB AAS Indonesia Surakarta, 2024)
Two of the many factors that can influence good or bad service quality are good organizational culture and a work environment that is comfortable, clean, and can provide peace of mind for both workers and customers. This study aims to examine the influence of Organizational Culture and Work Environment on Service Quality at Alfamart which are spread throughout Indonesia. Different from previous studies, this research adds the Job Satisfaction variable as a moderating variable. This research is quantitative research with an explanatory approach. This study uses secondary data distributed through questionnaires to 300 Alfamart employees spread throughout Indonesia with a minimum criteria of having worked for 2 years. The data used in this research were analyzed using Alt Samrt PLS 3.0. The results showed that each of the Organizational Culture and Work Environment variables had a positive and significant effect on the Service Quality variable. Apart from that, the Job Satisfaction variable is able to moderate the two independent variables above and has a quite significant shift in value.